2006
DOI: 10.1007/s10533-005-5632-y
|View full text |Cite
|
Sign up to set email alerts
|

Fine Roots vs. Needles: A Comparison of 13C and 15N Dynamics in a Ponderosa Pine Forest Soil

Abstract: Plant allocation patterns may affect soil C and N storage due to differences in litter quality and the depth of plant C and N inputs into the soil. We studied the dynamics of dual-labeled ( 13 C/ 15 N) Pinus ponderosa needles and fine roots placed at two soil depths (O and A horizon) in a temperate conifer forest soil during 2 y. Input of C as fine roots resulted in much more C retained in soil (70.5 ± 2.2% of applied) compared with needle C (42.9 ± 1.3% of applied) after 1.5 y. Needles showed faster mass loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
113
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 50 publications
13
113
0
1
Order By: Relevance
“…Measures of radiocarbon in classes of phospholipid fatty acids from microbial cell walls, however, show that microbes consume C substrates with a range of 14 C ages. Similar results have been observed with 13 C and 15 N labeled litter added to soil (Bird and Torn 2006).…”
Section: Microbial Fractionationssupporting
confidence: 87%
See 1 more Smart Citation
“…Measures of radiocarbon in classes of phospholipid fatty acids from microbial cell walls, however, show that microbes consume C substrates with a range of 14 C ages. Similar results have been observed with 13 C and 15 N labeled litter added to soil (Bird and Torn 2006).…”
Section: Microbial Fractionationssupporting
confidence: 87%
“…Since roots comprise a large fraction of plant inputs to soil, and soil C decomposition decreases with depth, the depth-distribution of root inputs affects soil C storage. All of these attributes have large effects on the transformation and stabilization of organic matter (Steinmann et al 2004;Bird and Torn 2006;Zanelli et al 2006). …”
Section: Organismsmentioning
confidence: 99%
“…As outlined above, we estimate that in total, \ 2% of root-litter carbon losses were via DOC, thus we conclude that in this Mediterranean grassland ecosystem litter losses are overwhelmingly dominated by heterotrophic respiration. This contrasts sharply with a laboratory incubation study utilizing a variety of soil types in which DOC was found to account for at least 20% of the carbon losses , but agrees with (a) a similar field study in a coniferous forest with a Mediterranean climate (Bird and Torn 2006) that found minor movement of litterderived DOC to deeper soil horizons, and (b) a recent field study in a temperate forest (Santos et al 2016) that found less than 1% of applied root-litter carbon in DOC collected from zero-tension lysimeters below the litter burial depth.…”
Section: Discussionsupporting
confidence: 54%
“…However, this approach introduces artifacts, such as restricting the physical contact of litter with the soil matrix. Moreover, unless the litter material is isotopically labeled, this approach it limited because it does not provide information on the fate of litter that is not recovered in the litterbag (e.g., Bird and Torn 2006;Cotrufo et al 2015;Hatton et al 2015). Isotopic techniques provide a method to trace the fate of rootlitter carbon into solid, dissolved, and gaseous forms (Bird and Torn 2006;Santos et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Isotopic analyses and comparisons of root and shoot biomarkers confirm the dominance of root-derived molecular structures in soil 43 and of root-derived carbon in soil microorganisms 44 . Preferential retention of root-derived carbon has been observed in temperate forests 45,46 , for example, where belowground inputs, including fungal mycelia, make up a bigger fraction of new carbon in SOM than do leaf litter inputs 44,47 . In addition to many above-ground inputs being mineralized in the litter layer, root and mycorrhizal inputs have more opportunity for physico-chemical interactions with soil particles 40 .…”
Section: Soil Humic Substancesmentioning
confidence: 99%